PENINGKATAN GURU DALAM KETERAMPILAN CALISTUNG DI MASA PANDEMI COVID-19 PADA SISWA KELAS II DI MI AL-ISHLAH KALIPARE - Imriti; Nanik Ulfa (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
This research is motivated by the level of stability of student learning outcomes in calistung skills in class students at MI Al-Ishlah Kalipare in the future covid-19 pandemic. Of course, in this case there are also some obstacles in the activities of the learning procsess. These obstacles are not only influenced by external factors but also internal factors so that seen from the unsatisfactory student learning, the teacher provides efforts to keep student enthusiasm for learning. So with regard to existing phenomena, teacher innovate to train calistung culture with bound books in improving calistung class II student.